Tachycardia-dependent left posterior hemiblock. Issue 6 (December 1981) - Chimienti, M; Salerno, J A; Tavazzi, L
Abstract : A patient with intermittent tachycardia-dependent left posterior hemiblock is reported. Electrocardiographic patterns of complete and incomplete block were documented. Identification of the electrocardiographic characteristics of intraventricular conduction defects is aided when they are intermittent. The difficulty in diagnosing incomplete left posterior hemiblock, and the possible masking of the signs of previous inferior infarction by left posterior hemiblock are emphasised.